PERILAKU PROFESIONAL TENAGA KESEHATAN DAERAH PESISIR PADA PELAYANAN KESEHATAN PRIMER PUSKESMAS BATU PANJANG KABUPATEN BENGKALIS TAHUN 2014 - Indra Fakhreza; Dedi Afandi; Dani Rosdiana (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Puskesmas as primary health care and development agent needs to be improved, especially in coastal settlement. This improvement depends on professional behavior of its health care workers. The aim of this research is to discover the professional behavior of health-care workers of Selat Baru community health care (Puskesmas), Bengkalis Regency, that was reflected by the six elements of professionalism. The design of this research uses exploration method with qualitative approaches on seven health-care workers of Puskesmas Batu Panjang, Bengkalis Regency, who were selected by using snowball sampling method. Data collection was done by interview and recorded with an audio recorder. The result of this research showed that all the informants possess altruism, accountability, excellence, duty, honor and integrity, and respect for other. In general, all of the Batu Panjang community health center (puskesmas) health-care workers possess the elements of professional behavior in carrying their duty, especially in providing service for the patients.Key word : professional behavior, health-care workers